Anisomeriini diving beetles—an Atlantic–Pacific Island disjunction on Tristan da Cunha and Robinson Crusoe Island, Juan Fernández? - Moriniére, Jérome (2015)
Anisomeriini diving beetles contain only two enigmatic species, representing a remarkable disjunction between the Pacific Juan Fernández Islands (Anisomeria bistriata) and the South Atlantic Tristan da Cunha Archipelago (Senilites tristanicola). They belong to the Colymbetinae, which contain 140 species worldwide. Here we aim to reconstruct the evolutionary history of the Anisomerinii and use > 9000 bp DNA sequence data from 13 fragments of 12 loci for a comprehensive sampling of Colymbetinae species. Analyses under different optimization criteria converge on very similar topologies, and show unambiguously that Anisomeria bistriata and Senilites tristanicola belong to the Neotropical Rhantus signatus species group, a comparatively recent clade within Colymbetinae. Anisomeriini therefore are synonomized with Colymbetini and both species are transferred to Rhantus accordingly, resulting in secondary homonymy of Rhantus bistriatus (Brullé, 1835) with Rhantus bistriatus (Bergsträsser, 1778). We propose the replacement name Rhantus selkirki Jäch, Balke & Michat nom. nov. for the Juan Fernández species. Presence of these species on remote islands is therefore not relictary, but the result of more recent range expansions out of mainland South America. Finally, we suggest that Carabdytini should be synonymized with Colymbetini. Our study underpins the Hennigian principle that a natural classification can be derived only from the search for shared apomorphies between species, not from differences.